Co-hydrothermal carbonization of pretreatment lignocellulose biomass and polyvinyl chloride for clean solid fuel production: Hydrochar properties and its formation mechanism. Issue 1 (February 2022) - Xue, Yixian; Bai, Li; Chi, Mingshu; Xu, Xiuling; Chen, Zhao; Yu, Kecheng; Liu, Zhi
Abstract: The production of coal as an alternative to solid fuel through co-hydrothermal carbonization (co-HTC) of polyvinyl chloride (PVC) and lignocellulose biomass can play a key role in improving the environment and energy supply. However, how to improve the synergistic effect of the reaction is still an urgent problem. In this study, the co-HTC method of acid-base pretreated straw and PVC was proposed to improve the synergistic effect of the reaction. Through the comparison and analysis of the products, the change of reaction mechanism and the reason for the increase of synergistic effect were speculated. The results showed that these pretreatment methods could effectively enhance the synergistic effect of the co-HTC process. Alkali pretreatment destroyed the connection between hemicellulose and lignin, increased the relative content of cellulose, accelerated the hydrothermal reaction, and increased the energy density of the product. The HHV of hydrochar increased from 26.89MJ/kg to 30.83MJ/kg and the energy recovery efficiency reached 68.85% by using base modified straw powder (BSP). Acid pretreatment destroyed the connection between cellulose and hemicellulose in straw, degraded part of lignin into phenols, which strengthened the substitution reaction of Cl in the co-HTC process and improved the dechlorination efficiency of the product. The chlorine content of hydrochar decreased from 7.84% to 6.44% and the carbon retention reached 84.49% by using acid-modified straw powder (ASP). The ICP-OES analysis showed that more insoluble metal salts in hydrochar were dissolved in solution, which reduced the risk of slagging and corrosion when hydrochar as a substitute for coal combustion. Graphical Abstract: The co-hydrothermal carbonization method of acid-base pretreatment of straw and polyvinyl chloride to improve the synergistic effect of the reaction. ga1 Highlights: The synergistic effect of co-HTC of PVC and acid-base pretreatment straw was studied. Base pretreatment can accelerate the co-HTC and increase the product energy density. Base pretreatment can increase HHV of the product from 26.89MJ/kg to 30.83MJ/kg. Acid pretreatment can increase the dechlorination efficiency of the product from 91.95% to 92.22%. Alkali pretreatment is better for fuel heat release, acid pretreatment is better for fuel clean use.